Генетическая структура вида Macrosiphum gei Koch, 1855, в Беларуси - Воробьева, М.М.; Супранович, П.К.; Воронова, Н.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. Aphids Macrosiphum gei Koch, 1855, are interesting objects for studying of speciation processes, because they are represented as a complex of forms in Belarus, that associated with different forage plants, viz Geum urbanum L., Chaerophillum aromaticum L., Aegopodium podagraria L., Anthriscus sylvestris L. Moreover, according to previously conducted studies, these forms differ in morphological signs and mitochondrial sequences gene COI. Methods. Methods for analysis of non-coding (STR) and highly conserved (COI) DNA were used to study the level of genetic structure of species and variability of aphids M. gei. Results. The аnalysis of nucleotide sequences of COI aphids, collected from different forage plants, revealed two haplotypes. The first one was seen in aphids collected from Ch. aromaticum and A. podagraria, and the second one was seen in aphids collected from G. urbanum and A. sylvestris. In the analysis of phylogenetic relationships determined that the aphid M. gei generates a complex inside of which different forms educes, that are associated with different forage plants. The analysis of microsatellite loci is an evidence of genetic differences between the samples collected from Ch. aromaticum and G. urbanum. Conclusions. These results allow us to assume that there is a currently divergence of aphids M. gei several independent groups in accordance with the preferred food plant. Keywords: aphids, Macrosiphim gei Koch, genetic variability, microsatellite loci, COI.